Pengaruh Pemahaman Investasi, Modal Minimal, dan Return terhadap Minat Mahasiswa Berinvestasi di Pasar Modal Syariah: Studi pada Mahasiswa Perbankan Syariah UIN Alauddin Makassar - Mohammad Alfin; Nuraeni Nuraeni; Supriadi Supriadi; Kamaruddin Kamaruddin; Sitti Fatimah (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
Students' interest in investing in the Islamic capital market has continued to increase alongside the growth of financial literacy and easier access to investment services. However, investment decisions remain influenced by investment knowledge, the availability of minimum investment capital, and expectations of investment Returns. This study aims to analyze the effects of investment knowledge, minimum investment capital, and investment Return on students' investment intention in the Islamic capital market. A quantitative explanatory approach was employed using primary data collected through questionnaires distributed to 50 students of the Islamic Banking Study Program, Faculty of Islamic Economics and Business, UIN Alauddin Makassar, selected through purposive sampling. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, partial and simultaneous hypothesis testing, and the coefficient of determination. The results indicate that the research instruments are valid and reliable, while the regression model satisfies all classical assumptions. Partially, investment knowledge and minimum investment capital have a positive effect on students' investment intention, whereas the effect of investment Return follows the statistical testing results. Simultaneously, all three variables significantly influence investment intention. These findings emphasize the importance of strengthening investment education, improving investment accessibility, and fostering realistic Return expectations to encourage students' participation in the Islamic capital market.